Implementation of the flipped classroom–based blended learning model in Indonesian language and literature learning in higher education - Suhardi Kasim; Yusrina Yusrina; Adityarini Kusumaningtyas (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2026)
Indonesian Language and Literature learning in higher education continues to face challenges related to limited student engagement and the underdevelopment of critical and argumentative thinking skills, particularly in discourse-based courses such as discourse analysis and academic debate. These challenges indicate the need for learning models that are pedagogically responsive and technologically adaptive. This study aims to implement a blended learning model using the flipped classroom approach to improve the quality of the learning process and students’ learning outcomes in Indonesian Language and Literature courses. The study employed Classroom Action Research with a cyclical design adapted from Pelton and was conducted collaboratively with a course lecturer. The research participants were sixth-semester students of the Indonesian Language and Literature Education program enrolled in the Indonesian Discourse Analysis course. The data comprised qualitative and quantitative data collected through classroom observations, interviews, documentation, field notes, and students’ learning outcomes across instructional cycles. Data were analyzed using descriptive, qualitative, and quantitative techniques. The findings indicate that implementing the flipped classroom-based blended learning model led to gradual and sustained improvements in student engagement, the quality of academic discussions and debates, and overall learning outcomes. The study concludes that the flipped classroom-based blended learning model is effective in fostering a more dialogic, reflective, and student-centered learning environment, as well as in strengthening students’ critical and argumentative thinking skills in Indonesian Language and Literature learning at the higher education level.